EKSPERIMENTASI MODEL PEMBELAJARAN KOOPERATIF TIPE TEAMS GAME TOURNAMENT (TGT) DAN MAKE A MATCH (MM) DENGAN PENDEKATAN SAINTIFIK PADA MATERI HIMPUNAN DITINJAU DARI KEMAMPUAN PENALARAN SISWA KELAS VII SMP NEGERI DI KABUPATEN SRAGEN TAHUN PELAJARAN 2014/2016 - Safitri, Rini Dewi; Mardiyana, Mardiyana; Usodo, Budi (Jurnal Pembelajaran Matematika, 2016)
Abstract: The purpose of this study was to determine the effect of learning models on the learning achievement in Mathematics viewed form reasoning ability of the students. The learning models compared were learning model of the scientific Teams Games Tournament (TGT), scientific Make a Match (MM), and scientific classical. The type of this study was a quasi-experimental study with a 3x3 factorial design. The population was all grade VII students of Public Junior High Schools in Sragen Regency. Sample was collected by stratified cluster random sampling. Instruments used for data collection were mathematics achievement test and reasoning ability questionnaire. The data analysis technique used was the two-way ANOVA with unequal cell. The conclusions of the study were as follows. (1) The mathematics learning achievement of students treated with TGT-PS learning model was better than that of those treated with MM-PS learning model and K-PS learning model. the mathematics learning achievement of students treated with learning model was as good as that of those treated with K-PS learning model. (2) The mathematics learning achievement of students with high reasoning ability was better than that of those with medium reasoning ability and low reasoning ability. The mathematics learning achievement of students with medium reasoning ability was better than that of those with low reasoning ability. (3) In TGT-PS learning model, the learning achievement of students with high reasoning ability was as good as that of those with medium reasoning ability, and that of those with high reasoning ability was better than that of those with low reasoning ability, and that of those with medium reasoning ability was as good as that of those with low reasoning ability. In MM-PS and K-PS learning models, the learning achievement of students with high reasoning ability was better than that of those with medium reasoning ability and low reasoning ability. And that of those with medium reasoning ability was as good as that of those with low reasoning ability. (4) In students with high reasoning ability and low reasoning ability, the students treated with TGT-PS model had the same learning achievement to those treated with MM-PS model, the students treated with TGT-PS model had the same learning achievement to those treated with K-PS model, the students treated with MM-PS model had the same learning achievement to those treated with K-PS model. In students with medium reasoning ability, the students treated with TGT-PS model had better learning achievement to those treated with K-PS model. The students treated MM-PS model had the same learning achievement to those treated with K-PS learning model.Keywords: Cooperative Learning, Teams Games Tournament, Make a Match, Classical Learning, Scientific Approach, Reasoning ability.